Author Correction: Pancreatic cancer: Circulating Tumor Cells and Primary Tumors show Heterogeneous KRAS Mutations. Issue 1 (December 2017) - Kulemann, Birte; Rösch, Stephanie; Seifert, Sindy; Timme, Sylvia; Bronsert, Peter; Seifert, Gabriel; Martini, Verena; Kuvendjiska, Jasmina; Glatz, Torben; Hussung, Saskia; Fritsch, Ralph; Becker, Heiko; et al.
Abstract A correction to this article has been published and is linked from the HTML version of this paper. The error has been fixed in the paper.